SOSIALISASI DAN DEMONTRASI UNJUK KERJA BEL SEKOLAH OTOMATIS DI SDN 5 KERAMAS - Agung, I G.A.P.R.; Setiawan, I. N.; Sukadarmika, G.; Hartawan, I G.A.K. D. D. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
The purpose of community service to be performed in SDN No. 5 Keramas is to socialize and show how to operate the automatic school bell arduino based microcontroller equipped with a real-time source DS1307 RTC IC and seven segment display to show the time. How to socialize is by demonstrating directly in front of the headmaster and several teachers at SDN 5 Keramas. This automatic school bell will sound like an electric bell manually only timed in accordance with school hours at SDN 5 Keramas. The bell rang long-time when school hours is started or hour first lesson is started, school hours after the first and second break and after school hours finishing. When would break the school bell rang too long. When the school hours changeover school bell rang shortly. Automatic school bell is also equipped with a manual mode by moving the swtch auto to manual. Manual mode is used when the condition / certain activities happened in schools such as the current general tests or when cleaning the school. Before being installed at SDN 5 Keramas automatic school bell has been tested for a week and has been running according to the timetable in SDN 5 Keramas. Once operated 1 month school bell has been able to work according to the timetable in SDN 5 Keramas.